2012
DOI: 10.1002/chem.201104015
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of Branched Silanes: A Computational Study on Mechanisms

Abstract: The initial steps of the thermal decomposition of silanes in the gas phase were examined by DFT-B3LYP calculations, with particular attention being paid to the way in which the reactivity pattern changes with the degree of branching of the silane. Besides the established pathways-1,2-hydrogen shift, H(2) elimination, and homolytic dissociation-1,3-hydrogen shift was also explored as an initial reaction step which leads to disilene structures. Subsequent silylene insertion and initial steps of radical chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…through isomerization of the disilene. Tri-and tetrasilane decompose thermally to produce similar species at reduced temperatures, compared to lower order silanes [3][4][5][6][7][8]. to a-Si films [2].…”
Section: Growth Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…through isomerization of the disilene. Tri-and tetrasilane decompose thermally to produce similar species at reduced temperatures, compared to lower order silanes [3][4][5][6][7][8]. to a-Si films [2].…”
Section: Growth Modelmentioning
confidence: 99%
“…Alternatively, using higher order silanes, via CVD and PECVD resulted in incremental benefits to deposition temperature, rate and efficiency at the lab-scale. This approach has not yet been scaled to manufacturing levels, possibly due to the inconsistency in silane vaporization [3][4][5][6][7][8]. For an example, Chung et al, studied Si film deposition using neopentasilane (NPS) via lowpressure CVD, and found enhanced growth rates [4].…”
Section: Introductionmentioning
confidence: 99%
“…There were a number of ab initio studies of the structural properties of Si 2 H 6 e.g., 46-53 as well as of the formation and reactions involving this molecule. [54][55][56][57][58] Agrawal et al 53 produced a global ab initio potential energy surface of disilane and used it to investigate the dissociation dynamics with classical trajectories. Márquez et al 50 reported a force field for Si 2 H 6 .…”
Section: Introductionmentioning
confidence: 99%
“…46,60 These structures are nominally asymmetric (C s symmetry) but essentially acquiring the C 3v symmetry. Thermal decomposition of Si 2 H 6 has been extensively studied, both theoretically (mostly using RRKM, Rice-Ramsperger-Kassel-Marcus) and experimentally, with the reaction Si 2 H 6 → SiH 2 + SiH 4 as the most common 53,56,57,61 and important decomposition process of the excited disilane 53,57,[62][63][64][65][66] , and where Arrhenius parameters and rate constants have been reported (e.g. Bowrey and Purnell 61 , Martin et al 63 , Mick et al 65 , Roenigk et al 67 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the decomposition temperature decreases with increasing number of silicon atoms in the silane ( Scheme ). [ 1 ] Therefore, silanes with higher molecular weight allow more efficient CVD processes, i.e., lower deposition temperatures and higher deposition rates. Furthermore, other ways of processing instead of CVD are possible with liquid silanes.…”
Section: Introductionmentioning
confidence: 99%